Use of Gamification for Adult Physical Rehabilitation in Occupational Therapy; A Novel Concept? - Sharon Zlotnik; Patrice L. (Tamar); Daphne Ruth Raban; Adina Houldin-Sade (SAGE Publishing, 2023)
Aim: This commentary discusses the concept of 'gamification' as referred to implicitly or explicitly in the occupational therapy literature. Although occasionally noted to be a new frontier for occupational therapy, our analysis suggests that game mechanics and gamification elements are, in fact, a 'road long traveled' by occupational therapists and that gamification evokes the core aims and vision of occupational therapy. Gamification has been implicitly incorporated into the occupational therapy literature for years, and its benefit of enhancing therapeutic outcomes is evident in many instances. We contend that a more explicit use of the term gamification within the occupational therapy literature will lead to a framework in which both practitioners and researchers can structure and evaluate therapeutic outcomes.